Sistem Sistem Pengisian Baterai Pada Mobil Listrik Menggunakan Panel Surya Dan PLN: Sistem Pengisian Baterai Pada Mobil Listrik Menggunakan Panel Surya Dan PLN - Jefri Lianda; Abdul Hadi; Adam; Zulfan Efendi; Ismail Budiman; Gusti Eviani (ABEC Indonesia, 2023)
Electric cars are an alternative in reducing environmental pollution due to combustion products. Electric cars require lead acid batteries as a substitute for fuel oil, so a battery charger is needed that can speed up charging and be safe. This research uses two sources of battery charging, namely PLN and solar panels. When the electric car is operated, the charger system is from solar panels while the charger with PLN energy is used when the weather is cloudy or the electric car is parked at home. Charging the battery in this electric car uses 2 MPPT units and one intelligent battery charger unit. MPPT conduct electric current from the solar panels to the battery at a maximum of 3.3 Amperes. Charging the battery from 40% level to 100% level takes 5 hours. Irntelligent battery charger flows current from the PLN source to the battery. The time needed to charge the battery from 40% to 100% level for 5 hours. The largest battery charging current from a PLN source is 10.5 A while from a solar panel is 3.3 A.